COMPLEX APPRAISAL OF WORKING CONDITIONS OF WORKERS IN SHAKE-OUT AND CHOP-CLEANING DEPARTMENTS OF CASTHOUSES - A. M. Lazarenkov; S. A. Horeva (Литьë и металлургия)
The complex appraisal of working conditions in shake-out and chipping-cleaning departments of casthouses is given. The results of appraisal of working conditions in shake-out and chipping-cleaning departments of casthouses are given